The pulsed‐dye laser as an adjuvant treatment modality in acne vulgaris: a randomized controlled single‐blinded trial - Karsai, Syrus; Schmitt, Laurenz Christofer; Raulin, Christian (British journal of dermatology, 2010)
Acne vulgaris is the most common skin disease and can pose a substantial therapeutic challenge. Recently, several phototherapeutic modalities, most notably pulsed‐dye laser (PDL) treatment, have been introduced, but the published results - albeit promising - are controversial.Objectives To assess the efficacy of an adjuvant PDL treatment when combined with a proven topical treatment [fixed‐combination clindamycin 1%-benzoyl peroxide 5% hydrating gel (C/BPO)].